India Economic Update, September 2012 - World Bank (Washington, DC, 2017)
Real gross domestic product (GDP) growth has slowed to a nine year low of 6.5 percent for FY2011-12, from 8.4 percent in the two previous years. The slowdown was most pronounced in the industrial sector, and more specifically in manufacturing and mining. In the quarter ending in June 2012, industrial output growth as measured by the Index of Industrial Production (IIP) has been negative. The contraction was particularly pronounced in the production of capital goods, which is in line with falling investment demand on the expenditure side of the National Accounts. The current account deficit reached a record 4.2 percent of GDP in FY2011-12, because of decelerating export growth and high crude prices. Merchandise exports grew by 41 percent in September 2011, but their growth slowed to 2 percent by August 2012 (measured as 12-months cumulative exports compared with the same 12 months of the previous year). Inflation reached 7.6 percent in August 2012. This represents a marked slowdown since September 2011, but there has been an uptick in food prices in recent months. Also, higher domestic prices for fuel, which are necessary to rein in spending on subsidies, will contribute to inflationary pressure. Inflation is therefore expected to reach 8 percent at end-March 2013. Real GDP growth is forecast to reach around 6.0 percent in FY2012-13, after 5.3 percent growth Q4 of FY2011-12 and 5.5 percent growth in Q1 of FY2012-13. The slowdown is at least partly caused by structural problems. These include power shortages, which are partly caused by the financial difficulties facing the electricity sector as discussed in the special topic section of this update, the corruption scandals that have hit the mining and telecom sectors, investor uncertainty because of pending changes in legislation (mining, taxes, land acquisition), and the tightening constraints of land and infrastructure. Tighter macroeconomic policies, slow growth in the core Organization for Economic Co-operation and Development (OECD) countries, and worries about another global recession also weigh on growth. Important signals to revive domestic growth drivers to lift sentiment more than produce instant efficiency gains could come from reforms recently announced and, more importantly, the reform of direct taxes, the implementation of the long-delayed Goods and Services Tax (GST), and passage of the land acquisition and mining bills. This update also looks closely at two important topics for medium- and long-term growth, namely India's Right to Education (RTE) Act, which aims to shape elementary education, and the financial difficulties in the Indian power sector.